Preparation and Characterization of (SBA-15)-Rhodamine B Host-Guest Nanocomposite Material - Zhai, Qing-Zhou; Yang, Dong (Asian Journal of Chemistry, 2010)
In the present study, SBA-15 molecular sieve was prepared by a hydrothermal method using the triblock copolymer poly (ethylene glycol)- block-poly(propyl glycol)-block-poly (ethylene glycol) (EG20PG40EG20) as a template and tetraethyl orthosilicate as silica source. Rhodamine B (RhB) nanoclusters have been successfully prepared in the channels of the SBA-15 molecular sieve host and a (SBA-15)-RhB host-guest nanocomposite material was prepared by liquid grafting method. By means of chemical analysis, powder X-ray diffraction, infrared spectroscopy, low-temperature nitrogen adsorption-desorption technique, solid state diffuse reflectance absorption spectroscopy and luminescence studies, the host-guest nanocomposite material was characterized. The results suggested that the guest RhB was successfully encapsulated in the channels of the host SBA-15 molecular sieve and the frameworks of the molecular sieve in the prepared composite materials were retained and highly ordered. The prepared host-guest nanocomposite material (SBA-15)-RhB shows luminescence and it may used as luminescence material.